1996
DOI: 10.1159/000177088
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Atrial Function after Atrial Fibrillation of Different Etiological Origins

Abstract: In order to evaluate atrial function after the restoration of normal sinus rhythm in patients with atrial fibrillation, an echocardiographic study was performed in 60 patients hospitalized for atrial fibrillation that was subsequently converted to sinus rhythm. The study population consisted of 60 patients, 41 males and 19 females, with a mean age of 67 ± 8 years. In etiological terms, 20 patients had atrial fibrillation with no associated pathology, 20 had an underlying ischemic cardiopathy an 20 had hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 14 publications
1
23
0
1
Order By: Relevance
“…Multiple studies have used this parameter as an index of LA function assessment, but it is affected by age and loading conditions. 317,[374][375][376][377][378][379][380][381][382] The PV atrial reversal velocity has also been used as a measurement of LA function. 317,377,[379][380][381][382] In the presence of reduced LV compliance and elevated filling pressures, atrial contraction results in significant flow reversal into the PVs.…”
Section: Left Atrial Function By Doppler Echocardiographymentioning
confidence: 99%
“…Multiple studies have used this parameter as an index of LA function assessment, but it is affected by age and loading conditions. 317,[374][375][376][377][378][379][380][381][382] The PV atrial reversal velocity has also been used as a measurement of LA function. 317,377,[379][380][381][382] In the presence of reduced LV compliance and elevated filling pressures, atrial contraction results in significant flow reversal into the PVs.…”
Section: Left Atrial Function By Doppler Echocardiographymentioning
confidence: 99%
“…9 -11 Prospective studies have confirmed a delayed restoration (days to weeks) of atrial contractile function after the return of normal electrical activity in almost all patients with chronic AF. [7][8][9][10][11] Transient atrial dysfunction may be important in the process of atrial stunning, which is believed to play a role in thromboembolic complications among AF patients after rhythm reversion. [12][13][14] The mechanisms of atrial contractile dysfunction after conversion of AF are poorly understood.…”
mentioning
confidence: 99%
“…In a previous paper we found an earlier recovery of atrial function in patients with atrial fibrillation alone compared to patients with ischemic and hypertensive diseases. 14 In the present evaluation the cause of atrial fibrillation did not influence atrial mechanical function. Harjai …”
Section: Clinical and Echocardiographic Variables Influencing Recovermentioning
confidence: 40%